2012
DOI: 10.1021/nn300327c
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Enhanced and Size-Dependent Generation of Reactive Oxygen Species from Protoporphyrin IX

Abstract: Photosensitizer, protoporphyrin IX (PpIX), was conjugated with Au nanoparticles (Au NPs) of 19, 66, and 106 nm diameter to study the size-dependent enhancement of reactive oxygen species (ROS) formation enabled by Au NPs. The ROS enhancement ratio is determined to be 1:2.56:4.72 in order of increasing Au NP size, in general agreement with theoretically calculated field enhancement to the fourth power. The convergence of the experimental and simulated results suggests that Au NP-enhanced and size-dependent ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(116 citation statements)
references
References 51 publications
2
113
1
Order By: Relevance
“…It was found that the nanoparticles were taken up through lysosomal mechanisms and caused ∼50% cell death due to apoptosis [31]. Porphyrin derivatives such as Photofrin and protoporphyrin IX have been formulated in several different nanoparticle systems such as metal oxide, chitosan, polymeric, silica and gold nanoparticles (examples shown in Figures 3A and 3B) [3253]. While majority of these formulations have envisioned the EPR mechanism to be utilized to passively target solid tumors, some have utilized receptor-mediated active targeting to enhance cell-selective delivery.…”
Section: In Vitro and In Vivo Investigations In Nanoparticle-basedmentioning
confidence: 99%
“…It was found that the nanoparticles were taken up through lysosomal mechanisms and caused ∼50% cell death due to apoptosis [31]. Porphyrin derivatives such as Photofrin and protoporphyrin IX have been formulated in several different nanoparticle systems such as metal oxide, chitosan, polymeric, silica and gold nanoparticles (examples shown in Figures 3A and 3B) [3253]. While majority of these formulations have envisioned the EPR mechanism to be utilized to passively target solid tumors, some have utilized receptor-mediated active targeting to enhance cell-selective delivery.…”
Section: In Vitro and In Vivo Investigations In Nanoparticle-basedmentioning
confidence: 99%
“…54 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 30 The viability of cells was determined by the thiazolyl blue tetrazolium bromide (MTT, Sigma) assay. Briefly, the cells after different treatments were incubated with 0.5 mg/mL MTT in cell culture medium for 2 h at 37 °C.…”
Section: Cellular Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…13 Another porphyrin derivative, protoporphyrin IX was reacted with a positively charged branched polyethyleneimine on the surface of gold nanoparticles yielding water stable nanostructures useful for PDT. 14 Zaruba et al attached two porphyrin-brucine conjugates to 3-mercaptopropanoic acid modified gold nanoparticles (ca. 14.7 nm) yielding two types of porphyrin-stabilised nanoparticles that could be dispersed in culture media and that were tested for PDT both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%